Cinema, trance and cybernetics - Holl, Ute (Recursions: theories of media, materiality, and cultural techniques., 2017)
We've all had the experience of watching a film and feeling like we've been in a trance. This book takes that experience seriously, explaining cinema as a cultural technique of trance, one that unconsciously transforms our perceptions. Ute Holl moves from anthropological and experimental cinema through nineteenth-century psychological laboratories, which she shows developed techniques for testing, measuring, and classifying the mind that can be seen as a prehistory of cinema, one that allows us to see the links among cinema, anthropology, psychology, and cybernetics.